MENELAAH PENERAPAN PEMBELAJARAN SOSIAL EMOSIONAL DAN PERWUJUDANNYA DALAM PENDIDIKAN YANG BERPIHAK PADA PESERTA DIDIK - Sudarsono, Mahadi; Rohmawati, Laili Indah Sari; Firdaus, Maylia; Habsy, Bakhrudin Al (Universitas Muria Kudus, 2024)
Education is an effort to shape individuals with characters aligned with the prevailing societal values. Consistent with the thoughts of Ki Hadjar Dewantara, education prioritizes the interests of the learners. One of the efforts in character formation is through social-emotional learning. Social-emotional learning encompasses five components: self-awareness, self-management, social awareness, social skills, and decision-making. This study examines how social-emotional learning is implemented in schools and its manifestation in learner-centric education. The method employed in this study is qualitative through literature review. Data collection techniques involve documentation by gathering various readings or literature. The results of this study indicate that there are already numerous effective implementations of social-emotional learning in schools. Additionally, the realization of social-emotional learning is an effort towards character formation in accordance with the needs of the learners.